1999
DOI: 10.1021/jm991091h
|View full text |Cite
|
Sign up to set email alerts
|

Amide Analogues of Trichostatin A as Inhibitors of Histone Deacetylase and Inducers of Terminal Cell Differentiation

Abstract: Inhibitors of histone deacetylase (HD) bear great potential as new drugs due to their ability to modulate transcription and to induce apoptosis or differentiation in cancer cells. We have described previously analogues of the complex natural HD inhibitors trapoxin B and trichostatin A with activities in the submicromolar range. Here we report structure-activity relationship analyses of further analogues of trichostatin A with respect to in vitro inhibition of maize HD-2 and their ability to induce terminal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
0
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 179 publications
(162 citation statements)
references
References 26 publications
6
151
0
5
Order By: Relevance
“…The semiquantitative prediction of cellular activity was not as consistent in this series as compared to the amide analogues of trichostatin A (2). 18 The amides are mostly moderately active in the Friend leukemic cells, but better predictive results are obtained in the ester series with the good inhibitors 11l,n being also among the most active compounds in cell culture. While the difference in cellular activity cannot be attributed to a simple difference in lipophilicity, still a differential uptake of these compounds might be a reason for the observed results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The semiquantitative prediction of cellular activity was not as consistent in this series as compared to the amide analogues of trichostatin A (2). 18 The amides are mostly moderately active in the Friend leukemic cells, but better predictive results are obtained in the ester series with the good inhibitors 11l,n being also among the most active compounds in cell culture. While the difference in cellular activity cannot be attributed to a simple difference in lipophilicity, still a differential uptake of these compounds might be a reason for the observed results.…”
Section: Resultsmentioning
confidence: 99%
“…18 This had not necessarily to be the case as maize HD-2 is structurally quite different from mammalian HDACs 33 and has been attributed to a HDAC class of its own, which is called class III. 5 The latter term has also been used for the newly discovered class of the NAD + -dependent Sir family.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study suggest that the hydroxamic acid end moiety of SAHA might be associated with moderate physicochemical properties and overall pharmacokinetic behavior compared to mercaptoacetamides. The thiol functionality has been shown to be a good replacement for hydroxamic acid, since zinc ion is highly thiophilic and thiol derivatives have been documented to inhibit zinc dependent enzymes including matrix metalloproteinases and angiotensin converting enzyme (Jung et al, 1999;Michaelides et al, 2001;Pikul et al, 2001;Remiszewski et al, 2002Suzuki et al, 2004. Also it has been demonstrated that the disulfide bond in the depsipeptide, FK228, was reduced within the cells, releasing the zinc binding thiol moiety and resulting in HDAC inhibition (Furumai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…25 These assumptions are due to the absence of structural elements that favor binding to the tubulin deacetylase domain as well as to the absence of an ortho-aminobenzamide element (favoring binding to the HDAC domain). The HDAC6 selective M344 (16b) is a good inducer of terminal cell differentiation in Friend leukemia cells 17 and of γ-globin expression in a promotor assay and in human erythroid cell cultures. 29 Its more HDAC1 selective homologue M360 (16c) mainly exerts an antiproliferative activity in these assays.…”
Section: Discussionmentioning
confidence: 99%